Expanding Borders in Kurdistan Region: Local and Regional Perspectives - Harith Qahtan Abd Allah; Abbas Fadel Atwan (Tikrit Journal For Political Science, 2017)
The expansion of borders in the Kurdistan Region has been a contentious issue, with significant implications at both the local and regional levels. The Kurdish Regional Government's attempt to incorporate additional territories, particularly those previously liberated from ISIS, has sparked debates and garnered diverse perspectives. At the local level, proponents of expanding borders argue that these territories are of historical and cultural significance to the Kurdish people. They view the boundaries as a non-negotiable part of their identity and emphasize the sacrifices made to reclaim them from ISIS. This perspective asserts that incorporating these areas into the Kurdistan Region is crucial for safeguarding Kurdish interests and ensuring their political and economic autonomy. However, there are also voices of dissent within the local population. Critics express concerns about the potential consequences of expanding borders, including demographic shifts, strained resources, and political instability. Some fear that such a move could exacerbate ethnic tensions and lead to conflicts with non-Kurdish communities residing in these areas. Regionally, the perspectives on the expansion of Kurdistan's borders vary. Neighboring countries, such as Turkey, Iran, and Syria, have expressed strong opposition to the idea. They fear that it could embolden Kurdish separatist movements within their own territories and destabilize the region. These countries have also raised concerns about potential implications for their own national security and territorial integrity. On the other hand, there are regional actors who are more supportive or adopt a more nuanced stance. Some argue for diplomatic engagement and negotiation to address the Kurdish aspirations within the framework of existing borders. They emphasize the need for peaceful dialogue and respect for international law to prevent further escalations and find mutually agreeable solutions.